Karakteristik Hidrolisat Protein Tambelo (Bactronophorus sp.) yang Dihidrolisis Menggunakan Enzim Papain - Okmawati, Lely; R, Rosmawati (Jurusan Biologi UIN Alauddin Makassar, 2013)
Tambelo is one type of wood eating worm that live in the dead mangrove tree and suffered a decomposition process. Tambelo who lived in a wooden rod Rhizophora sp has a sweet taste and very good for consumption. Tambelo nutrient content showing potentially in the development of highquality aquatic products, but this has not been done. In order tambelo can be used widely, it is necessary to make a new innovation in processing Tambelo meat into new face. Tambelo meat processing in a protein hydrolyzate as a source of flavor enhancer, which not only serves to create a sense of savory (umami) in food but also provides the role of nutrition and safe for the body considered very precise.This study aimed to examine the potential characteristics tambelo protein hydrolyzate (Bactronophorus thoracites). The experiment was conducted in two stages, the first stage of making a protein hydrolyzate treated hydrolyzate time (1, 2 and 3 hours) using the papain enzyme 0.5% (w/w) and temperature of 550C, pH 7. The best results are based on the content of the highest total protein become a reference in the second stage of the process. The second stage is a producing flavor enhancer, which further analyzed to measure the percentage of yield, amino acids, fatty acids and components of flavor. Proximate analysis to measure the highest total protein content of tambelo meat which hydrolyzed by the papain enzyme with optimum concentration at temperature of 55 ° C, pH 7. One hour hydrolysis showed the highest total protein content of 22.09% ± 0.19, yield hydrolyzate produced from the best treatment is 53.29% ± 7.36, hydrolysis process runs perfect for being able to produce 17 kinds of amino acids consisting of essential amino acids and non-essential with increased levels, and the hydrolysis process causes a significant fatty acid composition decreasing.Keywords: hydrolysis, papain enzyme, Tambelo protein